Promoting Mental Health in The Digital Age: Exploring the Effects of Social Media use on Psyhcological Well-Being - Ika Rahayu Satyaninrum; Falimu; Prasetio Rumondor; Hartin Kurniawati; Adit Mohammad Aziz (Westscience Press, 2023)
This study examined the influence of social media use on the psychological well-being of adolescents in West Java, Indonesia, in the digital age. A mixed methods approach was used, combining quantitative surveys and qualitative interviews to collect comprehensive data. Quantitative analysis showed that higher social media use was associated with lower self-esteem, increased body image dissatisfaction, higher levels of depression, and greater anxiety among adolescents. Qualitative findings highlighted the negative impact of social comparison, cyberbullying, and pressure to maintain a curated online image. The integration of the findings provides a nuanced understanding of the complex relationship between social media use and adolescents' psychological well-being. The results of this study have implications for theory and practice, emphasizing the need for targeted interventions and strategies to promote positive mental health outcomes in the context of social media use.